The effect of multi-ingredient intra- versus extra-cellular buffering supplementation combined with branched-chain amino acids and creatine on exercise-induced ammonia blood concentration and aerobic capacity in taekwondo athletes - Krzysztof Durkalec-Michalski; Krzysztof Kusy; Natalia Główka; Jacek Zieliński (Taylor & Francis Group, 2021)
Background This study aimed to investigate the effect of multi-ingredient intra- (BA) versus extra- (ALK) cellular buffering factor supplementation, combined with the customary intake of branched-chain amino acids (BCAA) and creatine malate (TCM), on body composition, exercise variables, and biochemical and hematological parameters in 9 elite taekwondo athletes. Methods Eight-week randomized double-blind crossover BA (5.0 g·day−1 of β-alanine) versus ALK (0.07 g·kgFFM −1·day−1 of sodium bicarbonate) supplementation combined with BCAA (0.2 g·kgFFM −1·day−1) and TCM (0.05 g·kgFFM −1·day−1) during a standard 8-week taekwondo training period was implemented. In the course of the experiment, body composition (dual X-ray absorptiometry), aerobic capacity (ergospirometric measurements during an incremental treadmill test until exhaustion), and exercise blood biomarkers concentrations were measured. Data were analyzed using repeated measures within-between interaction analysis of variance with the inclusion of experimental supplementation order. Results The maximum post-exercise blood ammonia concentration decreased in both groups after supplementation (from 80.3 ± 10.6 to 72.4 ± 10.2 µmol∙L−1, p = 0.013 in BA; from 81.4 ± 8.7 to 74.2 ± 8.9 µmol∙L−1, p = 0.027 in ALK), indicating reduced exercise-related adenosine triphosphate degradation. However, no differences were found in body composition, aerobic capacity, blood lactate concentration, and hematological parameters after neither BA (combined with BCAA and TCM) nor ALK (combined with BCAA and TCM) supplementation. Conclusions In highly trained taekwondo athletes, neither extra- nor intracellular buffering enhancement resulting from BA and ALK supplementation, combined with BCAA and TCM treatment, affects body mass and composition, maximum oxygen uptake, and hematological indices, even though certain advantageous metabolic adaptations can be observed.